2015
DOI: 10.1007/s00418-014-1305-z
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal expression of Math6 during mouse embryonic development

Abstract: The basic helix-loop-helix transcription factor Math6 was shown to have important regulatory functions during many developmental events. However, a systematic description of Math6 expression during mouse embryonic development is up to now still lacking. We carried out this study to show Math6 expression at different stages of mouse embryonic development aiming to provide a wide insight into the regulatory functions during the mouse organogenesis. Using immunohistochemistry, we could show that Math6 expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 20 publications
5
17
0
Order By: Relevance
“…To receive first insight into the role of Atoh8 in skeletal development, we investigated its detailed expression pattern in mouse skeletal tissues. Whole-mount in situ hybridization of E12.5 embryos confirmed the expression in early limb buds ( Fig 1A and B) [13,14]. In order to determine the specific expression of Atoh8 in chondrocytes, we compared its expression to that of Col2 and Col10, markers of proliferating and hypertrophic chondrocytes, respectively.…”
Section: Atoh8 Is Expressed In Proliferating and Hypertrophic Chondromentioning
confidence: 55%
See 1 more Smart Citation
“…To receive first insight into the role of Atoh8 in skeletal development, we investigated its detailed expression pattern in mouse skeletal tissues. Whole-mount in situ hybridization of E12.5 embryos confirmed the expression in early limb buds ( Fig 1A and B) [13,14]. In order to determine the specific expression of Atoh8 in chondrocytes, we compared its expression to that of Col2 and Col10, markers of proliferating and hypertrophic chondrocytes, respectively.…”
Section: Atoh8 Is Expressed In Proliferating and Hypertrophic Chondromentioning
confidence: 55%
“…Here we have investigated the role of Atoh8, a less well characterized member of the protein family, which is widely expressed in the developing embryo [8,9,14,38,39].…”
Section: Discussionmentioning
confidence: 99%
“…ATOH8 is a bHLH transcription factor expressed in a variety of different tissues such as brain, heart, skeletal muscle, kidney and pancreas (Lynn et al 2008 ; Wang et al 2015 ). Functional analyses have revealed that it regulates the differentiation of neural precursors (Inoue et al 2001 ), pancreas precursor cells (Lynn et al 2008 ) and podocytes (Ross et al 2006 ) and the development of retina and muscles (Balakrishnan-Renuka et al 2014 ; Yao et al 2010 ), and other tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Atoh8 has recently also been identified as a novel oncogene candidate as it shows abnormal DNA copy number in glioblastoma multiforme (Freire et al 2008 ). In mouse, it is expressed widespread in various types of tissues and organs, suggesting its multiple roles in different cellular contexts (Wang et al 2015 ). It is proposed that Atoh8 expression may be regulated by tissue-specific bHLH transcription factors in different cellular contexts so that it can play exclusive roles in different developmental events (Pujadas et al 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…As a new LSS-response molecule, atonal bHLH transcription factor 8 (ATOH8) is reportedly induced by 10 dyn/ cm 2 LSS in endothelial cells [16]. In addition, ATOH8 is also involved in mechanical factors regulation in multiple biological processes, including angiogenesis [16], skeletal muscle formation [17], and embryonic development [18]. Besides, in previous researches, ATOH8 expression among tumours is heterogeneous, and its role as a tumour suppressor or tumour promoter is still controversial.…”
Section: Introductionmentioning
confidence: 99%